The ersatz elevator - Snicket, Lemony (Snicket, Lemony. Series of unfortunate events, 2001)
The woeful saga of the Baudelaire orphans continues as evil Count Olaf discovers their whereabouts at Esme Squalor's seventy-one bedroom penthouse and concocts a new plan for stealing their family fortune.